Evaluation of tissue accumulation levels of advanced glycation end products by skin autofluorescence: A novel marker of vascular complications in high-risk patients for cardiovascular disease. (15th April 2015) - Yamagishi, Sho-ichi; Fukami, Kei; Matsui, Takanori
Abstract: A non-enzymatic reaction between reducing sugars and the amino groups of proteins, lipids and nucleic acids is known as the "Maillard reaction". The reactions have progressed in a normal aging process and at an accelerated rate under hyperglycemic, inflammatory, and/or oxidative stress conditions, thus leading to the formation and accumulation of advanced glycation end products (AGEs). Cross-linking modification of organic matrix proteins such as collagen by AGEs not only leads to an increase in vascular and myocardial stiffness, but also deteriorates structural integrity and physiological function of multiple organ systems. Furthermore, there is a growing body of evidence that interaction of AGEs with a cell surface receptor RAGE elicits oxidative stress generation and subsequently evokes inflammatory, thrombogenic and fibrotic reactions, thereby being involved in the development and progression of various age- or diabetes-related disorders, including cardiovascular disease (CVD), Alzheimer's disease, osteoporosis, cancer growth and metastasis. Skin AGE levels measured in biopsy specimens are associated with the development and progression of diabetic microangiopathy. Recently, accumulation levels of AGEs in the skin can be measured non-invasively by autofluorescence. Accumulating evidence has suggested that skin autofluorescence (SAF) is correlated with the presence and severity of vascular complications of diabetes and could predict future cardiovascular events and death in patients with diabetes. This review summarizes the pathophysiological role of tissue accumulation levels of AGEs in vascular damage in high-risk patients, especially focusing on the association between SAF and cardiorenal disorder. Graphical abstract: Highlights: AGEs play a role in CVD. Tissue AGE levels can be measured non-invasively by autofluorescence. SAF is associated with cardiorenal disorder.